Education and New Developments 2021 2021
DOI: 10.36315/2021end059
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in Digital Surroundings – Students Opinion on Digital Tools and Digital Lectures

Abstract: In today’s world, education in higher education institutions needs to use digital technologies to reach students without them being in the same room as the teacher. The “classical lecture”, with a teacher talking and writing on a blackboard interacting with students, has been in many ways exchanged with different digital or hybrid solutions. On one hand, it allows teachers to challenge their practices and try new ways of engaging students to learn, but on the other hand, it can be challenging to master differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This collection was gathered in November 2020 after students had a hybrid semester combining digital and non-digital lectures through different methods. The resultsfrom 57 studentsshowed some tendencies (Fojcik et al, 2021). Still, the authors decided to extend the survey to other campuses and professions to get more data.…”
Section: Data Collection and Description Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This collection was gathered in November 2020 after students had a hybrid semester combining digital and non-digital lectures through different methods. The resultsfrom 57 studentsshowed some tendencies (Fojcik et al, 2021). Still, the authors decided to extend the survey to other campuses and professions to get more data.…”
Section: Data Collection and Description Of Participantsmentioning
confidence: 99%
“…The change that higher education in Norway went through during the pandemic became an important topic for teachers and researchers, and many of them conducted research in this new situation. A survey, conducted one year after the start of the pandemic, asking students what kind of teaching they preferred, showed that 73% of the students wanted a physical lecture in a classroom with a teacher and classmates (Figure 1 after a year) (Fojcik, Fojcik, Kyte, Pollen, & Mjånes, 2021). Furthermore, 57 students responded wholly or partly to the survey, in which they evaluated teaching methods they were experiencing during the pandemic.…”
Section: Background and Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation